PENGARUH PENYULUHAN KESEHATAN TENTANG PROGRAM 3M-PLUS TERHADAP PENGETAHUAN DAN SIKAP MEMBERANTAS JENTIK NYAMUK AEDES AEGYPTI DI CANDI KARANG SLEMAN YOGYAKARTA - Asih Tri Utami; Dewi Utari; Agus Warseno (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Dengue hemorrhagic fever (DHF) is a major health problem in the community. According to WHO, 2.5-3 billion people were at risk of contracting DHF. InIndonesia, the incidence of DHF in 2013 was 90,245 people. One of the causes of DHF is a lack of awareness in performing routine activities such as 3M-Plus, a program to eradicate Aedes aegypti mosquito larvae. Objective:This research aimed to e x a m i n e t h e effect to health education about 3M-Plus program on knowledge and attitude to eradicate Aedes aegypti mosquito larvae in Candi Karang Sardonoharjo Ngaglik SlemanYogyakarta. Methods:This wasa quasi-experimental research with posttest only control group design.The number of samples in this study were 36 (18 intervention,18 control), which were selected using proportionate random sampling. Participants in the intervention g r o u p received two sessions of counseling regarding 3M-Plus program. Data were analyzed with Mann-Whitney test. Results: The level of knowledge and attitude of the intervention group was good after education session and lessin the control group. Mann- Whitney test obtained a p-value of.000<α0.05. Conclusion: There was an influence of health education about 3M-Plus program on knowledge and attitudes to eradicate Aedes aegypti mosquito larvae in Candi Karang Sardonoharjo Ngaglik Sleman Yogyakarta. Keywords:Health education,3M-plus program